Communication, Collaboration, Critical Thinking, and Creative (4Cs) in TVET: A Bibliometric Analysis and Systematic Literature Review - Taqwa, Muhammad Reyza Arief; Roozafzai, Zahra Sadat; Suhendi, Endi (Universal Education, 2026)
This article maps research trends, key contributors, and thematic structures of the 4Cs—communication, collaboration, critical thinking, and creativity—within Technical and Vocational Education and Training (TVET), while synthesizing experimental efforts to enhance these skills. It addresses a documented gap by combining bibliometric performance analysis and science mapping (RQ1–RQ6) with a systematic review of intervention studies (RQ7). A total of 3,246 documents were obtained, of which 1,655 documents were analyzed bibliometrically, and 32 documents were analyzed through a systematic literature review after screening and applying inclusion/exclusion criteria. The 4Cs–TVET research shows a continuous surge with “communication skills” as the driving theme and creativity relatively unexplored, indicating a thematic focus that still leans toward social competencies. In general, 4Cs–TVET research involves many researchers from various institutions and countries, showing that this research has become a global focus. However, the findings indicate that participation is concentrated in developed and middle-income countries, whereas least developed countries (LDCs) remain underrepresented in this research area. Experimental efforts to improve the 4Cs are spread across five approaches (technology/online, collaborative-interprofessional, gamification, project-based/active learning, simulation), but 56.25% target only one skill—collaboration being the most dominant—and only 6.25% integrate all 4Cs, indicating the need for more holistic intervention design.